2004
DOI: 10.1021/ja049214x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Highly Fluorescent Indolizino[3,4,5-ab]isoindoles

Abstract: We report here the synthesis, X-ray structures, optical and electrochemical properties, fabrication of light-emitting devices, and density functional calculations for indolizino[3,4,5-ab]isoindole (INI) derivatives. Strongly luminescent heterocycles based on the INI unit were synthesized by 1,3-dipolar cycloaddition reactions between pyrido[2,1-a]isoindole (PIS) and acetylene or ethylene derivatives. They are indolizino[3,4,5-ab]isoindoles 2-9 and 14-15, benzo[1',2'-1,2]indolizino[3,4,5-ab]isoindoles 10, pyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 65 publications
(45 reference statements)
3
61
0
1
Order By: Relevance
“…[47][48] Frontier orbital theory may provide an explanation for such behavior. [50] In 2, the HOMO is associated with the phen ligands and Zn II orbitals, and the charge transitions of the tetranuclear metal cores may play an important role in the change of the Fe II /Fe III oxidation potential. The HOMO in 1 is located in the FMPA 2À groups, so the Fe II centers of 1 are more easily oxidized to Fe III than those in complex 2.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[47][48] Frontier orbital theory may provide an explanation for such behavior. [50] In 2, the HOMO is associated with the phen ligands and Zn II orbitals, and the charge transitions of the tetranuclear metal cores may play an important role in the change of the Fe II /Fe III oxidation potential. The HOMO in 1 is located in the FMPA 2À groups, so the Fe II centers of 1 are more easily oxidized to Fe III than those in complex 2.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The synthesis and the biological applications of fluorescent compounds have previously been investigated. [3][4][5][6][7][8] It has been shown that the quinone/hydroquinone redox couple can interconvert reversibly by exchanging two protons and two electrons. This characteristics enables it to serve as an antenna or the control subunit, which affects the absorption or the emission optical properties of the compound.…”
mentioning
confidence: 99%
“…The starting materials 4a-4c were prepared by the 1,3-dipolar cycloadditions of isoquinolinium carboxymethylide with the corresponding alkynes. [16] Their reactions with 1 under the same conditions as described above for the reactions of 2a-2k with 1 gave the corresponding benzo [6,7]pyrrolizino [3,4,5-ab]isoquinolines 5a-5c as red solids, respectively, in 52-60 % yield ( Table 2). Compounds 5a-5c have strong molecular ion peaks in their MS spectra, with 5b and 5c having this peak as the base peak.…”
Section: Introductionmentioning
confidence: 92%
“…[7] Therefore, further investigation of their luminescence-structure rela-properties of these compounds have been investigated by cyclic voltammetry. Indolizino [3,4,5-ab]isoindoles without a substituent at C-2 (compounds 3a, 3c, 3d) or with an alkyl substituent in the framework (3i, 3k) undergo irreversible anodic oxidations and reversible cathodic reductions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation